Rapid Implementation of Telegenetic Counseling in the COVID-19 and Swedish Healthcare Context: A Feasibility Study - Pestoff, Rebecka; Johansson, Peter; Danielsson, Henrik; Neher, Margit; Gunnarsson, Cecilia (Frontiers in Health Services, 2022)
This study reports the process and preliminary findings of rapid implementation of telegenetic counselling in the context of Swedish healthcare and COVID-19 pandemic, from both a patient and a provider perspective. Fourty-nine patients and 6 healthcare professionals were included in this feasibility study of telegenetic counselling in a regional Department of Clinical Genetics in Sweden. Telegenetic counselling is here defined as providing genetic counselling to patients by video (n=30) or telephone (n=19) appointments. Four specific feasibility aspects were considered: acceptability, demand, implementation, and preliminary efficacy. Several measures were used including the Genetic Counselling Outcome Scale 24 (collected pre- and post-counselling); the Telehealth Usability Questionnaire; a short study specific evaluation and Visiba Care evaluations, all collected post-counselling. The measures were analyzed with descriptive statistics and the preliminary results show a high level of acceptance and demand, from both patients and providers. Results also indicate successful initial implementation in the regional Department of Clinical Genetics and preliminary efficacy, as shown by significant clinically important improvement in patients’ empowerment levels.